Employee Performance Improvement Strategy Through Strengthening Employee Engagement, Organizational Support, and Work Motivation (Research Using Path Analysis and the SITOREM Method on Permanent Employees of PT Sun Tak Indonesia) - Ramdan Jaya; Soewarto Hardhienata; Yayan Hadiyat (Universitas KH. Abdul Chalim Mojokerto, 2025)
The research population was all permanent employees at PT. SUN TAK INDONESIA totaling 148 people, The results of the path analysis show a) there is a positive and significant direct influence of employee engagement and work motivation with a path coefficient value of β = 0.359, b) there is a positive and significant direct influence of organizational support and work motivation with a path coefficient value of β = 0.633, c) there is a positive and significant direct influence of work motivation and employee performance with a path coefficient value of β = 0.291, d) there is a positive and significant direct influence of employee engagement and employee performance with a path coefficient value of β = 0.303, e) there is a positive and significant direct influence of organizational support and employee performance with a path coefficient value of β = 0.399, f) there is a positive and significant indirect influence of employee engagement and performance through work motivation with a Zcount value of 2.556> Ztable 1.96 and a path coefficient of β = 0.104, it can be concluded that work motivation plays an effective role as a mediating variable, g) there is a positive and significant indirect influence of organizational support and performance through work motivation with a Zcount value of 3.049 > Ztable 1.96 and path coefficient of β=0.186, it can be concluded that work motivation plays an effective role as a mediating variable. The results of Sitorem's analysis show that the indicators of employee performance, employee engagement, organizational support, and work motivation that need improvement are: 1st; Providing Justice. 2nd; Working Conditions 3rd; Rewards from the Organization. 4th; Leadership Support. 5th; Career Development. 6th;Vigor. 7th; Concern for Productivity. 8th; Dedication. 9th; Ownership. 10th; Loyalty & Commitment. 11th; Absorption. 12th; Responsibility. 13th; Compensation. 14th; Achievement. 15th; Organizational procedures. 16th; Recognition. 17th; Working conditions. 18th; Status. 19th; Progress. 20th; Quality. 21st; Quantity. 22nd; Effectiveness. 23rd; Efficiency. 24th; Punctuality.